Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Perusahaan Jasa CV. Jaya Trans - Nursafitri, Gita; Ma'mun, Saepul; Sutira, Andri (Jurnal Pelita Nusa, 2023)
Consumer satisfaction is a customer's assessment of the use of goods or services compared to previous expectations. Factors that influence consumer satisfaction include service quality. This research aims to determine the level of service quality on consumer satisfaction. The research method uses quantitative descriptive, through a questionnaire distribution approach. The data collection technique uses purposive sampling with a population of 150 respondents and a sample of 60 respondents. Research shows that the results of the final condition of the service quality variable (X) are 60.72%, indicating that the level of service quality is included in the strong category. The results of the final condition of the consumer satisfaction variable (Y) are 59.95%, indicating that total consumer satisfaction is included in the strong category. The regression value of the service quality variable (X) on consumer satisfaction (Y) is Y = 10.045 + 0.822X. The results of calculating the correlation coefficient between variable X and variable Y show that the level of service quality is related to consumer satisfaction with a value of r = 0.696. The R Square value is 0.485, which means that the percentage contribution of the influence of variable X to Y is 48.5%. The results of the hypothesis test calculation show that tcount > ttable or 7.384 > 2.001 and the sig value. 0.000 < 0.05, then Ha is accepted and Ho is rejected, which means there is a positive and significant influence between the service quality variable (X) on the consumer satisfaction variable (Y) at CV. Jaya Trans. Keywords: Service Quality, Customer Satisfaction, Logistics Services.